Problem Kelembagaan Transisi Demokrasi Di Daerah - Kacung Marijan (Magister Ilmu Administrasi Publik, 2005)
Some scholars have focused their attention on the process of democratization at the local level They argue that democracy at the local level will encourage the emergence of democracy at the national level Furthermore, neo-institutionalism approach is important in supporting transition to democracy at the local level. The approach has applied particular policies, such as decentralization and strengthening local parliament, local government capacity, political culture and civil society. This approach, however, did not work properly. The interests of political and economic players at the local level often hamper the work of neo-institutonalism approach.